Networks of Innovation : Measuring Structure and Dynamics between and within Helices, Regions and Spatial Levels. Empirical Evidence from the Baltic Sea Region - Virkkala, Seija; Mariussen, Åge (Brill, 2021)
In the quantitative, macro-oriented triple helix literature, synergy is measured indirectly, through patent data, firm data and other secondary statistical sources. These macro-level quantitative studies do not open up for understanding how different processes of cooperation create different outcomes, in terms of synergies. This article presents an alternative method of measuring quantitatively how different networks of innovation in a variety of ways create different types of complex synergies. This opens up for an empirical analysis of variations of synergy formation, seen as innovation networks with different structures, formed within and between helices, regions and geographical levels. Data was collected through a snapshot survey in 10 regional cases in the Baltic Sea Region. The analysis presents how different networks of innovation within and between helices are formed by different combinations of expectations, experiences and gaps.
Keywords: Baltic Sea Region; Connectivity; Helix measurements; Innovation network; Luhmann; Synergy; fi=Aluetiede|en=Regional Studies|